2007
DOI: 10.1002/dvdy.21408
|View full text |Cite
|
Sign up to set email alerts
|

Developmental regulation of muscleblind‐like (MBNL) gene expression in the chicken embryo retina

Abstract: Muscleblind-like (MBNL) is a CCCH zinc finger-containing RNA-binding protein required for the development of both muscle and photoreceptors in Drosophila; it is conserved evolutionarily, and it is associated in humans with the muscular disease myotonic dystrophy. Its role in the development of vertebrate retinal cells, however, remains unknown. As an initial approach to its investigation, we have cloned three chick muscleblind genes, characterized their isoforms, and examined their expression patterns in the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 35 publications
4
11
0
Order By: Relevance
“…Consistent with what has been reported in nematodes (Norris et al, 2017), zebrafish (Machuca-Tzili et al, 2011) and chickens (Huang et al, 2008), we demonstrated cell-typespecific expression of mbl. Mbl was present in all cells tested that express Dscam2.10B and absent from Dscam2.10A cells.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with what has been reported in nematodes (Norris et al, 2017), zebrafish (Machuca-Tzili et al, 2011) and chickens (Huang et al, 2008), we demonstrated cell-typespecific expression of mbl. Mbl was present in all cells tested that express Dscam2.10B and absent from Dscam2.10A cells.…”
Section: Discussionsupporting
confidence: 92%
“…Minor disruptions can have profound consequences in the lens since it has little opportunity to repair or recover from defects in its highly ordered programme of differentiation. The Drosophila homolog of MBNL1, muscleblind, was originally isolated as a gene required for photoreceptor differentiation [45], while MBNL proteins have been demonstrated to be developmentally regulated in the chick retina [46]. Recent RNA sequencing data has implicated MBNL proteins as key negative regulators of transcriptional pathways involved in the maintenance of pluripotency in embryonic stem cells, with over--expression of MBNL proteins promoting alternative splicing patterns associated with differentiated cells [11].…”
Section: Discussionmentioning
confidence: 99%
“…An unexpected function for MBNL2 in cytoplasmic mRNA transport has been reported, 39 but it is not yet known whether MBNL1 can also perform this function. In embryonic chick retina development, MBNL1 and MBNL2 become distributed in different regions of the photoreceptor, 52 but it is not known whether they perform similar or different functions there. Nuclear foci in DM1 myoblast cultures were labeled by in situ hybridization, and creatine kinase (CK) was labeled with CK-JAC mAb ͓46͔.…”
Section: Discussionmentioning
confidence: 99%